Propuesta de restauración ecológica del área de protección de la nueva sede del Centro Nacional de Control de Energía (CENCE), San Miguel de Santo Domingo de Heredia, Costa Rica. - Ramirez-Campos, Norberto (Instituto Tecnológico de Costa Rica, 2015)
In this paper refers to the importance of ecological restoration, for the recuperation of degraded ecosystems product of different human activities. It has an area of old coffee plantations intended for forest protection by the National Center for Energy Control (CENCE), the main objective is to make a proposal for ecological restoration, aimed at attracting wildlife, soil protection and beautification landscape, for that identification of flora and fauna is also an investigation of the general characteristics of the land and its surroundings and determine the next steps in developing the proposal. We search for a nearby place and with similar conditions, belonging to the same area of life which allow assess your current ecosystem and serve as monitoring compared to ecological restoration that wants to establish model looking site.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2015.
Keywords: Flora; Fauna; Precipitación; Temperatura; Medio ambiente